2006
DOI: 10.29140/jaltcall.v2n3.30
|View full text |Cite
|
Sign up to set email alerts
|

CALL for autonomy, competency and relatedness: Motivating language learning environments in Web 2.0

Abstract: In the last 30 years, computer assisted language learning has gone through significant changes, as illustrated in Warschauer's taxonomy of structural, communicative and integrative CALL (Warschauer, 2000). Computer technology itself has greatly influenced these developments and prompted innovative applications. It seems that yet again new opportunities for CALL are emerging in what is labelled Web 2.0 in the computer world (O'Reilly, 2005).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 5 publications
(1 reference statement)
1
35
0
1
Order By: Relevance
“…Such a trend matches the three essential characteristics of the Web 2.0 technology, namely, personalisation, interactivity and collaborative content building (Millard & Ross, 2006). Web 2.0 offers affordances that can be designed as learning environments, enabling writers to become part of an active learning community (Alm, 2006;Franklin & Van Harmelen, 2007).…”
Section: Web 20 Technology and Wiki For Collaborative Writingmentioning
confidence: 99%
“…Such a trend matches the three essential characteristics of the Web 2.0 technology, namely, personalisation, interactivity and collaborative content building (Millard & Ross, 2006). Web 2.0 offers affordances that can be designed as learning environments, enabling writers to become part of an active learning community (Alm, 2006;Franklin & Van Harmelen, 2007).…”
Section: Web 20 Technology and Wiki For Collaborative Writingmentioning
confidence: 99%
“…Smith, 2000;Lowe & Williams, 2004;Bloch, 2007), and doing so seems to "stimulate investment… and engagement" and is seen as public and "playful" (Lowe & Williams, 2004). Many studies have suggested that blogging may increase learner interaction, autonomy, and fluency (Pinkman, 2005;Alm, 2006). While blogs have become extremely popular in L2 writing classes, to the author's knowledge, no studies have examined social bookmarking, which could become the reading equivalent to blogging.…”
Section: Social Bookmarking Sites For Ermentioning
confidence: 99%
“…Both teacher‐ and learner‐made computer visuals are quite extensively reported in Computer‐Assisted Language Learning literature, for instance, filming interviews (Gromik, 2006; Hanson‐Smith & Marzio, 2006), soap operas (Alm, 2006, 2008) or mini‐documentaries (Brooke, 2003), creating storyboard projects (Hazzard, 2006), authoring podcasts and vodcasts (Stanley, 2006), designing digital stories (Alexander & Levine, 2008; Banaszewski, 2002; Skinner & Hagood, 2008; Tendero, 2006). Such student‐made digital assets are used to present to their classroom peers for discussion and feedback.…”
Section: Introductionmentioning
confidence: 99%